Socio-Economic Condition of Occupation Changed for Majhi, Mushahar, and Bote Communities in Nawalpur District - Jaishi, Bishnu Prasad; Mahato, Bir Bahadur; Upadhayay, Govinda Raj (Madhyabindu Journal, 2026)
The primary objective of the study, which is called "Level of Satisfaction on Socio-Economic Condition of Occupation Changed for Majhi, Mushahar, and Bote Communities in Nawalpur District," is to look into the socioeconomic situation and level of satisfaction of the indigenous community in Nawalpur. This study, which uses a descriptive research design, chose a sample of 150 people from the rural and urban areas of Nawalpur's Majhi, Mushahar, and Bote communities. We used a standard set of questionnaires to collect the data. We used SPSS software to work with the data we gathered. 63% of people own their land, 78.30% own their home, 76% own their bank account, and 27.30% use the internet. These were the major findings after the change in occupation. It is strongly recommended that suitable policies be developed to enable indigenous communities to adapt their occupations in response to environmental changes, thereby enhancing their satisfaction with improvements in their socio-economic conditions, such as increased access to resources, training programs, and support for sustainable practices.